Efficacy of Mindfulness- and Acceptance-Based Treatments for Culturally and Linguistically Diverse Patients: Communicating This to Patients - Kimble, MS, Edward; Li, EdD, Chieh (North American Journal of Medicine and Science, 2017)
There is a growing consensus that the use of mindfulness- and acceptance-based behavioral therapies can result in physiological and psychological benefits in Clinical and non-Clinical populations. However, the research on the use of such therapeutic approaches with culturally and linguistically diverse (CLD) populations is still in its infancy. This article reviews the efficacy of mindfulness- and acceptance-based treatments in terms of physiological outcomes, as well as the evidence thus far for their efficacy with CLD groups. We also provide suggestions for communicating with CLD patients about the potential benefits of mindfulness- and acceptance-based approaches in the treatment of stress-related conditions. [N A J Med Sci. 2017;10(4):171-175. DOI: 10.7156/najms.2017.1004171]